Associação entre poluição do ar e composição corporal : revisão sistemática e metanálise - Oliveira, Suelen Goecks (2019)
Objective: Assess the association between pollution and body composition. Methods: The PECOS strategy was defined, in which “P” participants of any age, sex or ethnicity, “E higher level of environmental pollution, “C” lower level of environmental pollution, “O” body composition measurements and “S” longitudinal studies. We used the following sources to identify relevant studies from inception to March of 2022: MEDLINE (via PubMed), EMBASE, Scientific Electronic Library Online, Latin American and Caribbean Health Sciences Literature, Scopus, Web of Science, SPORTDiscus and gray literature. Two review authors independently scanned and assessed the quality of the studies. Results: Of 1406 studies identified, 24 were included in the Systematic Review (SR) and 18 in the meta-analysis (MA). The 24 studies included 505,370 individuals from different age groups, 42 types of environmental pollutants, and 20 different measures of body composition. The MA for all pollutants, showed association with waist circumference was β 0.97 (95% CI 0.77 to 1.18; I2: 98%), the sum of skinfolds was β 1.03 (95% CI 0.90 to 1.16; I2: 59%) and trunk fat percent was β coefficient -0.05 (95% CI -0.10 to -0.01; I2: 0%). On the other hand, the MA differentiated by pollutant found an association with of Diclorodifenildicloroetileno and the Sum of 4 Skinfolds was β 1.09 (95% CI 0.99 to 1.18; I2: 0%), of hexachlorobenzene and the BMI Z was 0.44 (95% CI 0.15 to 0.73; I2: 0%) and of p.p-dicloro difenil tricloroetanol and the Body Fat Percentage was -0.38 (95% CI –0.74 to -0.02; I2: 0%). Finally, the MA by subgroup found an association between of pesticide and the waist circumference was β 1.0 (95% CI 0.79 to 1.21; I2: 98%); the Sum of 4 skinfolds was β 1.07 (95% CI 0.99 to 1.15; I2: 7%) and body fat percentage was β -0.48 (95% CI -0.67 to -0.30; I2: 0%). Heavy metals and Waist circumference was β 0.98 (95% CI 0.96 to 1.00; I2: 0%). Benzene derivate and Waist circumference was β 1.01 (95% CI 0.83 to 1.18; I2: 91%); of sum of four skinfolds was β 1.05 (95% CI 0.65 to 1.46; I2: 73%). Carbon-containing compounds and of Trunk fat was β -0.05 (95% CI -0.10 to -0.01; I2: 91%). Conclusion: environmental pollutants are associated with changes in body composition.